Bio-Simulation Studies of Valganciclovir Hydrochloride: Molecular Descriptor-Based QSAR Modelling and Swiss ADME Analysis Using in silico Models - Gangadhar, Yashavanth; Turaifi, Amal Rasul Al; Naveen, Nimbagal Raghavendra; Goudanavar, Prakash; Fattepur, Santhosh; Sreeharsha, Nagaraja; Islam, Mohammed Monirul; Chohan, Muhammad Shahzad (Indian Journal of Pharmaceutical Education and Research, 2025)
Aim To evaluate the pharmacokinetics and toxicity properties of Valganciclovir Hydrochloride, a potent antiviral agent, using in silico models. Background Valganciclovir Hydrochloride is an FDA-approved antiviral agent and understanding its pharmacokinetic and toxicological properties is critical for optimizing its use. Objectives To assess the pharmacokinetic properties, toxicity profile and bioactive characteristics of Valganciclovir Hydrochloride using computational in silico models. Materials and Methods Lipinski’s Rule of Five was applied to evaluate the compound’s solubility and intestinal absorption properties. The drug’s plasma protein binding and Blood-Brain Barrier (BBB) penetration were also assessed to understand its distribution profile. Clearance rates were calculated to evaluate how efficiently the compound is eliminated from the body. Additionally, the LD50 value of Valganciclovir Hydrochloride was estimated using a rat toxicity model to understand its toxicity threshold. Pharmacological activities were further assessed using the PASS online server to evaluate its bioactive properties and potential toxic effects on non-tumor cell lines. Results Valganciclovir Hydrochloride exhibited high solubility and a moderate rate of intestinal absorption. The drug showed low plasma protein binding and poor BBB penetration, suggesting that its distribution is primarily localized within the body. The compound demonstrated a low clearance rate of 5 mL/min/kg. Toxicity analysis revealed an estimated LD50 value of 3,080,000 mg/kg via the oral route, indicating a relatively high toxicity threshold. The PASS analysis highlighted various bioactive properties without any toxic effects on non-tumor cell lines, with a Probability of occurrence (Pa) value lower than 0.5, further supporting the non-toxic profile of the compound.
Keywords: In silico Modelling; Valganciclovir Hydrochloride; Pharmacokinetics; Toxicity Assessment; Molecular Descriptor; QSAR Modelling